Pharmacology of post-traumatic stress disorder - Кукушкін, Віталій Наумович; Кукушкін, В. Н.; Kukushkin, V. N; Tregub, Tamara; Lytvynenko, Marianna; Chebotarova, Svitlana; Oliynyk, Nina; Gulbs, Olga; Nazaryan, Rozana (My University, 2023)
The aim of this study was to evaluate current approaches to the pharmacotherapy of posttraumatic stress disorder. An information search was carried out in the databases PubMed, Ovid, EMBASE by keywords: “posttraumatic stress disorder”, “treatment”, and “medications”. Search depth 2012- 2022 years. From the general data (4877 articles) there were selected 14 articles with the highest degree of relevance. A content analysis of selected articles was carried out with the formation of recommendations for the use of pharmacotherapy in posttraumatic stress disorder. Currently, there are no unified approaches to the pharmacotherapy of posttraumatic stress disorder. Antidepressants (SSRI SNRIs) are primarily considered as first-line drugs, but only sertraline, paroxetine, and fluoxetine are approved by the FDA. But these drugs have a fairly wide range of side effects, including suicidal thoughts. The use of benzodiazepines should be limited as they increase the risk of developing posttraumatic stress disorder. Vortioxetine becomes a very promising option. The most significant benefits of vortioxetine are the significant positive effects of vortioxetine on attention, memory, and executive function. There is some evidence for the use of alpha-1 adrenoceptor antagonists and alpha-2 adrenoceptor agonists in therapy. In insomnia the use of prazosin and trazodone is recommended. Pharmacotherapy of posttraumatic stress disorder requires administration of medications with multimodal action. Currently, there are no unified approaches to the pharmacotherapy of posttraumatic stress disorder. Further randomized clinical trials are necessary for developing effective treatment of posttraumatic stress disorder.

Метою цього дослідження було оцінити сучасні підходи до фармакотерапії посттравматичного стресового розладу. Інформаційний пошук здійснювався в базах даних PubMed, Ovid, EMBASE за ключовими словами: «посттравматичний стресовий розлад», «лікування», «ліки». Глибина пошуку 2012-2022 рр. Із загальних даних (4877 статей) відібрано 14 статей з найвищим ступенем актуальності. Проведено контент-аналіз вибраних статей з формуванням рекомендацій щодо застосування фармакотерапії посттравматичного стресового розладу. Уніфікованих підходів до фармакотерапії посттравматичного стресового розладу на сьогодні немає. Антидепресанти (СИОЗС SNRIs) в основному розглядаються як препарати першої лінії, але тільки сертралін, пароксетин і флуоксетин схвалені FDA. Але ці препарати мають досить широкий спектр побічних ефектів, включаючи суїцидальні думки. Застосування бензодіазепінів слід обмежити, оскільки вони підвищують ризик розвитку посттравматичного стресового розладу. Вортіоксетин стає дуже перспективним варіантом. Найбільш істотними перевагами вортіоксетину є значний позитивний вплив вортіоксетину на увагу, пам’ять і виконавчу функцію. Існують деякі докази використання в терапії антагоністів альфа-1-адренорецепторів і агоністів альфа-2-адренорецепторів. При безсонні рекомендовано застосування празозину і тразодону. Фармакотерапія посттравматичного стресового розладу вимагає призначення препаратів мультимодальної дії. Уніфікованих підходів до фармакотерапії посттравматичного стресового розладу на сьогодні немає. Для розробки ефективного лікування посттравматичного стресового розладу необхідні подальші рандомізовані клінічні випробування.
Pharmacology of post-traumatic stress disorder / T. Tregub, M. Lytvynenko, V. Kukushkin, S. Chebotarova, N. Oliynyk, O. Gulbs, R. Nazaryan // Georgian medical news. - № 9 (342). – 2023. – P. 122 – 126. (Scopus)
Keywords: Post-traumatic stress disorder; Russo-Ukrainian war; pharmacotherapy; medications; treatment; Research Subject Categories::SOCIAL SCIENCES; Research Subject Categories::MEDICINE; Посттравматичний стресовий розлад; російсько-українська війна; фармакотерапія; ліки; лікування